Propaganda of the Bintang Timur Newspaper during the Indonesia-Malaysia Confrontation, 1963-1965 - Osman, Samsul Kamil; Haniffa, Mohamed Ali; binti Rambely, Nor Azlah Sham (JURNAL JAWI, 2024)
This survey study aims to review the propaganda activities of the Bintang Timur newspaper, published by the Indonesian Communist Party (PKI), during the Indonesia-Malaysia Confrontation from 1963 to 1965. The objective of this study is to examine how effectively the PKI utilized Bintang Timur to spread propaganda in order to gain public support for the movement to Ganyang Malaysia (Crush Malaysia). The propaganda, through articles and cartoons, successfully instilled hatred among the people towards the leaders and citizens of Malaysia. This study explores the Indonesian Communist Party's (PKI) role in the Indonesia-Malaysia Confrontation (1963-1965), using historical methodology and focusing on its political, social, and military involvement. Data is collected through library research, primarily examining newspapers published by the PKI. In addition to references at the National Library of the Republic of Indonesia, field studies such as interviews and observations were also conducted by the author. The study's findings show that the propaganda of the Indonesian Communist Party, through both written content and the use of cartoons, successfully influenced the Indonesian public to support President Sukarno's confrontation policy towards Malaysia. This public support was translated into backing for President Sukarno’s Ganyang Malaysia campaign.